Mud crab, Scylla tranquebarica (Fabricius, 1798), crablet grow‐out in lined ponds with different stocking densities to support soft‐shell crab production - Gunarto Gunarto; Herlinah Herlinah; Muliani Muliani; Nurbaya Nurbaya; Rosmiati Rosmiati; Emma Suryati; Sulaeman Sulaeman; Samuel Lante; Andi Parenrengi; Muhammad Nur Syafaat; Early Septiningsih; Idayanti Nursyamsi (Journal of the World Aquaculture Society)
Abstract Crab stocking densities in brackish water ponds can influence crab growth rate, survival, and production volume. This study aimed to determine the optimum grow‐out stocking density for Scylla tranquebarica crablets reared in lined ponds to supply the soft‐shell crab industry. Three stocking density treatments (1, 4, and 8 ind./m2) were applied to crablets reared in lined ponds for 90 days. The crablets were fed low‐value fish (Leiognathus equula) at an initial rate of 100% of total body weight for two weeks, reduced to 3% toward the end of the study. Crablets stocked at 1 and 4 ind./m2 had a significantly (p < 0.05) higher net growth (NG) and daily growth rate (DGR) than crablets stocked at 8 ind./m2. Deformed crabs were also most common at the highest stocking density. The intermediate stocking rate achieved moderate survival and feed conversion rates, with the highest crab production volume (19.65 ± 0.10 kg/100 m2) and net income (6845.60 US$/Ha/2 crops/year). Based on these findings, a stocking rate of around 4 ind./m2 is recommended for the grow‐out of S. tranquebarica crablets in lined ponds.